Illness episodes in a cohort of preterm infants in their first year of life - Muller, Seth (Department of Paediatrics and Child Health, 2021)
Background: There is limited data available regarding the illness episodes and hospital admissions of preterm infants after initial discharge in low- and middle-income countries. Objectives: To prospectively follow a cohort of HIV unexposed preterm infants (29-34 weeks) and describe their illness episodes, admissions and associated risk factors over a one-year period. Methods: The study was nested in a parent study evaluating the efficacy of a monoclonal antibody against RSV from Jan 2017 to March 2017. 53 infants were enrolled from two government neonatal nurseries in Cape Town, South Africa. Descriptive data were collected with regards to perinatal history and socioeconomic factors of the infants' household. All infants received careful follow-up. Logistic regression was performed to assess association between hospitalisation and socio-economic factors. Results: All 53 infants who were recruited were followed up over one year. There were 436 illness episodes of which 31 were hospital admissions. One infant died at home. The most common illnesses were respiratory (53%) and dermatological (17%) in nature. Lower respiratory tract infections accounted for 71% of all hospital admissions. There were no significant associations between socioeconomic subgroups when comparing illness episodes or hospital admissions. Conclusion: This is one of the few studies to record all illness episodes and not just admissions over a one-year period for HIV unexposed infants. There are high rates of intercurrent respiratory infection and hospitalisation of preterm infants in their first year of life. Public health interventions to reduce the risk of LRTI must be strengthened. Larger studies need to be done to be able to report on the associations with socioeconomic determinants in developing countries.